Dinamika Komunikasi Pengungkapan Kekerasan Seksual Anak Dalam Lingkungan Keluarga Perkotaan - Novrian; Sarwititi Sarwoprasodjo; Pudji Muljono; Krishnarini Matindas (Mediakom : Jurnal Ilmu Komunikasi, 2026)
Child sexual abuse remains a serious social issue in Indonesia, yet its communicative dimension is still rarely discussed in communication studies. This study examines how child survivors negotiate disclosure processes within urban family contexts using Communication Privacy Management Theory. A qualitative case study approach was employed involving survivors, family members, psychologists, social workers, and institutional actors in Bekasi City, Indonesia. Data were collected through in-depth interviews, observations, focus group discussions, and document analysis. The findings reveal that disclosure occurs gradually through selective communication, trust testing, and partial openness shaped by emotional safety and family relationships. Decisions to disclose or conceal information are strongly influenced by power relations, economic dependency, cultural stigma, and fear of social judgment. The study also identifies information boundary turbulence within family and institutional responses, including information leakage, repeated storytelling, and weakened survivor trust. These findings highlight that child protection requires trauma-informed communication, confidentiality management, and stronger interinstitutional coordination to create safer communication environments for child survivors in urban protection systems.